2021
DOI: 10.3390/en14164875
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Absorption Performance Evaluation of Water-Based Nanofluids (CNTs, Cu, and Al2O3) for Solar Thermal Harvesting

Abstract: For solar thermal harvesting, an experimental study was performed on the thermal absorption performance of water-based carbon nanotubes (CNTs), Cu, and Al2O3 nanofluids using a halogen lamp-based thermal radiation system. The effect of nanoparticle concentrations (0.01 wt.%, 0.1 wt.%, and 1 wt.%) on the nanofluid dispersion, stability, and thermal absorption characteristics was investigated, and a comparative analysis was performed for each type of nanofluid. All types of nanofluids increased the absorbance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Ansyss Fluent software used to carry out the simulation for different concentration particularly for 20 nm sized Al 2 O 3 nano particles and results were tabulated and compared to theoretical values with heat transfer coefficient and Nusselt number. Youngho Lee et al (2021), show that dispersion characteristics of oxide based nano-fluids Al 2 O 3 having high absorbance values with respect to the concentration for solar application, in his investigation thermal absorption increases for the concentration 0.01, 0.1%, 1% by weight. Kong and Lee (2020), investigated the thermal performances of Al 2 O 3 nano particles in water using circular tube under turbulence with three different concentrations and found that thermal conductivity and heat transfer coefficient of nano-fluid increased with increase in concentration in extend to this, he also shows that Nusselt number increases for Reynolds number 4000 to 24000.…”
Section: Introductionmentioning
confidence: 92%
“…Ansyss Fluent software used to carry out the simulation for different concentration particularly for 20 nm sized Al 2 O 3 nano particles and results were tabulated and compared to theoretical values with heat transfer coefficient and Nusselt number. Youngho Lee et al (2021), show that dispersion characteristics of oxide based nano-fluids Al 2 O 3 having high absorbance values with respect to the concentration for solar application, in his investigation thermal absorption increases for the concentration 0.01, 0.1%, 1% by weight. Kong and Lee (2020), investigated the thermal performances of Al 2 O 3 nano particles in water using circular tube under turbulence with three different concentrations and found that thermal conductivity and heat transfer coefficient of nano-fluid increased with increase in concentration in extend to this, he also shows that Nusselt number increases for Reynolds number 4000 to 24000.…”
Section: Introductionmentioning
confidence: 92%
“…The thermal absorption performance of nanofluids is another important characteristic of this colloidal mixture. Recently [114], an experimental study was performed to evaluate the thermal absorption performance of nanofluids of carbon nanotubes, Cu, and Al 2 O 3 using water with base fluid. The authors show that all nanofluids increased the absorbance and electrical conductivity with increasing nanoparticle concentration, which has improved the thermal absorption performance of nanofluids.…”
Section: Solar Panels and Collectorsmentioning
confidence: 99%